A prospective randomized trial to compare the effectiveness of honey vs. silver sulfadiazine dressing in burn wound management - Choudhary, K N; Mohanty, S K.; Soni, P (International Journal of Medical Research and Review, 2016)
Introduction: In tribal part of central India burn injuries is a major cause of morbidity and mortality. This trail carried out at Chhattisgarh institute of medical sciences, Bilaspur intended to evaluate the efficacy and outcome of local application of honey vs. conventional silver sulfadiazine dressing treatment of burn wound. Methods: The study encompasses 200 patient of burn injury of varied aetiology admitted in burn ward whose total body surface area of burn was 15% to less than 50%. The patient receiving local application of honey were in group I (n=100) and those with conventional silver sulfadiazine ointment dressing treatment formed group II (n=100). Honey local application dressing was done on alternate day for 6 weeks of follow up period. The major outcome was, complete healing after 6 weeks period, while wound healing status was assessed at 2 weeks interval. Result: 52 out of 100 subject in honey treated group achieved complete healing as compare to 16 out of 100 subjects in silver sulfadiazine treated group. There was significant decrease in wound surface area, pain score & increase in comfort score in honey treated group in comparison to silver sulfadiazine ointment treated group at 0.00 level of significance. Conclusion: Markedly inexpensive honey as local application is highly effective in achieving complete healing in burn wound and is a very use full alternative for burn wound management.